Enhancing target product profiles to meet rice processor needs for capacity utilization in Uganda’s seed product market segments - Twine, Edgar E.; Connor, Melanie; Malabayabas, Arelene J. B.; Oloo, Augustine (CGIAR, 2024)
The current study uses cross-sectional data from Ugandan rice millers to estimate capacity utilization, examine the correlation between milling different domestically sourced varieties and capacity utilization, as well as the varietal traits that are potentially associated with greater capacity utilization. Capacity utilization is the percentage of the installed milling capacity in rice mills currently being used, and it depends on, among other things, the rice varieties milled. The greater the consumer demand for a variety, the greater the miller demand for it. Varieties differ in milling quality characteristics, such as milling recovery (weight of milled rice relative to the weight of paddy milled), and head rice yield (weight of intact grains relative to the weight of paddy milled), both of which are important to capacity utilization and can be altered through breeding. However, little is known about milling capacity utilization associated with domestically grown rice varieties and factors related to capacity utilization. Capacity utilization among millers that procure/grow paddy to sell milled rice is 47 percent of installed capacity. Among the improved rice varieties released by the National Agricultural Research Organization (NARO) since 2002, only WITA 9, which largely belongs to the Rice 22 EAF seed product market segment (it is transplanted, medium-maturity, long and slender, soft-textured, and suitable for the rainfed lowland ecology) is associated with greater capacity utilization. The study also finds that milling of medium-length aromatic and nonaromatic rice could increase capacity utilization. Therefore, to alleviate the problem of low milling capacity utilization, the traits embodied in WITA 9 could be taken into consideration in developing target product profiles (TPPs) for Uganda’s seed product market segments. In addition, it might be necessary to breed for medium grain shape (length-to-width ratio of 2.1–3.0) and to develop both aromatic and nonaromatic varieties.